Unveiling Appearance and Ideology in the short story Overcoat by Ghulam Abbas: A Critical Discourse Analysis - Nazir, Sadia; Javed, Fareeha; Baig, Sana (Pakistan Languages and Humanities Review, 2025)
This study employs Fairclough’s three-dimensional framework for Critical Discourse Analysis (CDA) to analyze the short story Overcoat by Pakistani writer Ghulam Abbas. The analysis penetrates into how language, social identity, power relations, and ideological structures intersect in the story’s narrative to expose fundamental societal structures in Pakistani postcolonial society. By presenting a comprehensive textual, discursive, and social analysis of the narrative, this study unwraps how the elegant attire of the protagonist acts as a semiotic device to exhibit class identity, and how institutions like the hospital function serve as ideological disseminators. The findings reveal that the protagonist’s identity in Overcoat is socially negotiated and fluctuating, constructed and reconstructed through discourse. The findings suggest that CDA turns out to be an insightful lens to reveal the socio-political functions of the narrative.